Far-Field Pattern Reconstruction from Near-Field Data Collected via a Nonconventional Plane-Rectangular Scanning: Experimental Testing - Francesco D’Agostino; Ilaria De Colibus; Flaminio Ferrara; Claudio Gennarelli; Rocco Guerriero; Massimo Migliozzi (International Journal of Antennas and Propagation)
This paper deals with the experimental validation of an efficient near-field-far-field (NF-FF) transformation using the planar wide-mesh scanning (PWMS). Such a nonconventional plane-rectangular scanning technique is so named, since the sample grid is characterized by meshes wider and wider when going away from the center, and makes it possible to lower the number of needed measurements, as well as the time required for the data acquisition when dealing with quasi-planar antennas. It relies on the use of the nonredundant sampling representations of electromagnetic fields which employ an oblate ellipsoid or a surface formed by two circular “bowls” with the same aperture diameter but eventually different bending radii to shape a quasi-planar antenna. A two-dimensional optimal sampling interpolation formula allows the reconstruction of the NF data at any point on the measurement plane and, in particular, at those required by the classical NF-FF transformation with the conventional plane-rectangular scanning. The measurements, performed at the planar NF facility of the antenna characterization laboratories of Selex ES, have confirmed the effectiveness of this innovative scanning also from the experimental viewpoint.